OPTIMASI DESAIN SUDU TURBIN DENGAN PADUAN SAVONIUS DAN DARRIEUS UNTUK MENINGKATKAN DAYA - Dony Hidayat Al-Janan; Maulana Iwan Saputra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
In this study, the effectiveness of the combination of the Savonius and Darrieus wind turbines was investigated, which is a vertical axis wind turbine. The aim is to determine the optimal blade design and analysis of the combined blade design compared to the stand-alone design. The method used is CFD simulation to find the torque value used for power calculation. From all simulations, the highest torque and power occurred at a wind speed of 5.58 m/s. The simulation shows the Savonius, Darrieus, and Savonius-Darrieus combination turbine variations, - so then as result from the Savonius-Darrieus combination obtained the best results, namely the torque of 82.59 Nm and the power of 2194.41 W. In conclusion, the turbine model with a combined blade design produces better torque and power compared to stand-alone turbine models.